A revision of the Thyropygus allevatus group. Part 1: the T. opinatus subgroup (Diplopoda: Spirostreptida: Harpagophoridae) - Pimvichai, Piyatida; Enghoff, Henrik; Panha, Somsak (Zootaxa, 2009)
The Thyropygus opinatus subgroup of the T. allevatus group is revised. The T. opinatus subgroup corresponds to the genus Cornugonus Demange, 1961, which is formally synonymized under Thyropygus. Eight new species are described from Thailand: T. bearti n. sp., T. brachyacanthus n. sp., T. loxia n. sp., from Suratthani province, T. bispinus n. sp., from Uthaithani and Phrae provinces, T. bispinispatula n. sp., from Chumphon province, T. chelatus n. sp., from Nakhonsrithammarat province, T. cristagalli n. sp., from Phang Nga province and T. erectus n. sp., from Satun province. The other species of the T. opinatus subgroup, viz., T. opinatus (Karsch, 1881), n. comb., T. floweri (Demange, 1961), n. comb., T. implicatus (Demange, 1961), n. comb., and T. inflexus (Demange, 1989), n. comb., are redescribed. New records are given for T. opinatus, T. implicatus and T. floweri. The type locality of T. floweri is shown to be in Thailand rather than Malaysia.